Dispersal and transport of microplastics in river sediments. (15th June 2021) - He, Beibei; Smith, Mitchell; Egodawatta, Prasanna; Ayoko, Godwin A.; Rintoul, Llew; Goonetilleke, Ashantha
Abstract: Rivers are viewed as major pathways of microplastic transport from terrestrial areas to marine ecosystems. However, there is paucity of knowledge on the dispersal pattern and transport of microplastics in river sediments. In this study, a three dimensional hydrodynamic and particle transport modelling framework was created to investigate the dispersal and transport processes of microplastic particles commonly present in the environment, namely, polyethylene (PE), polypropylene (PP), polyamide (PA), and polyethylene terephthalate (PET) in river sediments. The study outcomes confirmed that sedimental microplastics with lower density would have higher mobility. PE and PP are likely to be transported for a relatively longer distance, while PA and PET would likely accumulate close to source points. High water flow would transport more microplastics from source points, and high flow velocity in bottom water layer are suggested to facilitate the transport of sedimental microplastics. Considering the limited dispersal and transport, the study outcomes indicated that river sediments would act as a sink for microplastic pollutants instead of being a transport pathway. The patchiness associated with the hotspots of different plastic types is expected to provide valuable information for microplastic source tracking. Graphical abstract: Image 1 Highlights: Microplastics with lower density have high mobility in sediments. Dense microplastics prone to accumulate close to source points in river sediments. High bottom water velocity result in longer transport of sedimental microplastics. Limited transport of benthic microplastics makes river sediments function as a sink. Patchiness in microplastics hotspots provide valuable data for source tracking. Abstract : Capsule: Modelling of transport processes of microplastics to understand their dispersal and fate in aquatic environments.